Do antifinalismo providencialista ao finalismo na natureza no pensamento de Espinosa - Andrelino Ferreira dos Santos Filho (2018)
Studies on Spinoza's thinking have in recent years provoked a profound debate about the criticism and refusal of the notion of teleology. Although no scholar of the subject disagrees on the rejection of the finalism of a providentialist nature, in relation to man and other entities the scope of the critique of finalism is not clear, which has demanded the effort of the researchers in order to establish the precise limit of criticism to the final causes doctrine. In order to make explicit the issue and at the same time to assess the positions in terms of extracting the outline of an interpretative position, the examination and comparison between the main scholars of the finalism was established. By the end of this examination, following the position that approximates the Spinozas finalism of an Aristotelian legacy, the Aristotelian finalism was investigated, in order to specify its nature and, in accurate way, to return to the text of Spinoza to discuss the effectiveness of the presence of elements in favor of an internal finalism to corporeal entities in general. It is the defense of the finalism intrinsic to the physical nature that, despite the refusal of it ends in nature, it seems sustainable. At last, this work aimed at finding in Spinozas physics, that was presented in the second part of Ethics and the Principle of Cartesian Philosophy, the supporting elements that nature, in the specificity of its particular entities, accommodates, to some degree, evidence of the presence of elements that can be interpreted teleologically, although it can not be denied the finalist theory refusal. Therefore, this thesisargues that Spinoza does not refuse the internal finalism (ends in Nature), but he opposes to the idea of the ends of Nature (divine providence), what means that the refusal of the attribution of ends to the Natura naturans does not imply the refusal of the existence of ends intrinsic to the entities in the Natura Naturata.